Sensitivity analysis of the effects of the thermal parameters of exhaust gases on the output of a thermoelectric generator. Issue 3 (3rd December 2018) - Mostafavi, Seyed Alireza; Taheri, Moein; Mahmoudi, Mojtaba
Abstract: Recovering the dissipated heat from exhaust is a useful means of reducing the energy consumption level as well as cutting down on environmental pollution. An efficient technique for recovering this lost heat is the use of thermoelectric generators, which directly convert the dissipated heat into useful electrical energy. In this paper, a whole thermoelectric generator system installed on the exhaust pipe of a vehicle has been modeled, and the effects of thermal parameters on the output of this thermoelectric generator have been measured and evaluated by means of sensitivity analysis. The E‐Fast sensitivity analysis method has been used in this study. The sensitivity analysis results indicate that, among the thermal parameters examined, the temperature of gases entering the heat sink installed at exhaust pipe outlet ( T hi ) has the greatest influence (37%) and the flow rate of fluid entering the heatsink installed on the cold side of thermoelectric modules ( m ̇ c ) has the second greatest influence (17%) on the output power of the considered thermoelectric generator. By using these results, the best cases of hot exhaust gases from various industries and vehicles with the highest potential of recovering the dissipated energy and heat from them by thermoelectric generators can be identified.